“Seven Complex Lessons in Education for the Future”, by Edgar Morin: A Look from Information Literacy - Oliveros Castro , Sergio (2023)
Seven Complex Lessons in Education for the Future (1999), by Edgar Morin, is a text that has marked educational knowledge for the last 23 years, expressing this document key elements to understand the human being from education and framing its existence in a context of constant changes at the technological level and planetary challenges where the shadow of extinction is permanently. It is against this scenario that Morin proposes seven key knowledge for human understanding today: Facing the blindness of knowledge, Feeding the principles of pertinent knowledge, Teaching the human condition, Teaching earthly identity, Facing uncertainties, Teaching the understanding and cultivating the ethics of the human race. In this writing, this knowledge is reflected from the perspective of information literacy, visualizing the importance of information in each of the knowledge indicated by Morin, highlighting the need of the human being to understand the processes of how it is created, used, it is refined and reused for information to generate new and better knowledge, which is founded on scientific and ethical principles that coincide with education.